Developing a sustainable tribal tourism model vis-a-vis the tribal region of Rajasthan - Vineet Chouhan (Journal of Tourism, Heritage & Services Marketing, 2022)
Purpose: The tourism industry in India is rising and has excellent potential to create jobs and produce a large amount of foreign capital, thereby promoting the region's overall economic and social growth. The inviting customs of tribal India, the diverse community and native culture are always drawing the attention of tourists. Sustainable tourism is an enterprise that aims to get a minimal effect on the atmosphere and native customs while helping to generate revenue, employment, and conserve local environments. Tribal tourism will promote the development of locally generated goods, apart from direct and indirect jobs, and have essential multiplier effects as money is recycled into communities. Also, the sector offers substantial improvements in the tribal region development with provincial taxes and encourages local and national infrastructure growth for India. This paper describes tribal tourism, sustainable tribal tourism, and its significance in the Indian scenario. Methods: Responses of 213 tribes were analysed with multiple regression to build a model for sustainable tribal tourism's success in Rajasthan. Results: Social, economic, environmental sustainability, facility and problems dimensions are found to have a positive impact on the sustainability in tribal tourism. Implications: This study has been conducted to acquaint the growth prospects in the form of social, economic, environmental and facility aspects and challenges of sustainable tribal tourism in India.
Keywords: Q01; Q56; M14; 330; Tribal tourism; sustainable tourism; cultural heritage